1999
DOI: 10.1016/s0741-5214(99)70139-4
|View full text |Cite
|
Sign up to set email alerts
|

Venographic comparison of subcutaneous low–molecular weight heparin with oral anticoagulant therapy in the long-term treatment of deep venous thrombosis

Abstract: The patients who were allocated to undergo enoxaparin therapy had a significantly greater improvement in their quantitative venographic score, a significantly lower recurrence rate of symptomatic venous thromboembolism, and a significantly lower incidence of bleeding than patients who underwent treatment with coumarin. LMWH can be used on an outpatient basis as a safer and more effective alternative to classical oral anticoagulant therapy for the secondary prophylaxis of selected patients with DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 26 publications
(36 reference statements)
2
66
0
8
Order By: Relevance
“…5,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Of these studies, the 13 most recent compared widely differing LMWH regimens with VK antagonists (INR 2.0 to 3.0) 5,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] or, in 1 small study, unfractionated heparin. 85 Three months of low-dose unfractionated heparin (5000 U twice daily) was inadequate treatment for proximal DVT.…”
Section: Alternatives To Vk Antagonists Unfractionated and Lmwhmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Of these studies, the 13 most recent compared widely differing LMWH regimens with VK antagonists (INR 2.0 to 3.0) 5,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] or, in 1 small study, unfractionated heparin. 85 Three months of low-dose unfractionated heparin (5000 U twice daily) was inadequate treatment for proximal DVT.…”
Section: Alternatives To Vk Antagonists Unfractionated and Lmwhmentioning
confidence: 99%
“…85 Three months of low-dose unfractionated heparin (5000 U twice daily) was inadequate treatment for proximal DVT. 82,83 Three or 6 months of unfractionated heparin 84,85 or LMWH, 5,[85][86][87][88][89][90][91][92][93][94][95][96] in doses that varied from one-third 5,86,89,90 to full [91][92][93][94]96 therapeutic doses were effective. A meta-analysis of 7 of these studies (total of 1379 patients) 5,86,88 -91,93 found 3 months of LMWH therapy associated with less recurrent VTE (odds ratio 0.7; 95% CI, 0.4 to 1.1) and less major bleeding (odds ratio 0.4; 95% CI, 0.2 to 1.1) than treatment with a VK antagonist for 3 months.…”
Section: Alternatives To Vk Antagonists Unfractionated and Lmwhmentioning
confidence: 99%
“…Nowadays, the ambulatory treatment of VTE is fully accepted by the medical societies of many Western European countries, and is administered to up to 80% of patients with venous thrombosis and 50% of patients with pulmonary embolism [20]. The newly published papers indicate the role of LMWH in the recanalisation of the thrombotic veins and the reduction of valvular incompetence rate, secondary to venous thrombosis [21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials proved that therapy with LMWH is efficient and safe both in the treatment and secondary prophylaxis of acute deep vein thrombosis, which may successfully be performed in the ambulatory setting [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The administration of LMWH significantly reduces the risk of complications and the ambulatory treatment costs, with relatively better outcome concerning the recurrence of venous thrombosis and pulmonary embolism [18][19][20][21]. The latest reports discuss the influence the LMWH has on the recanalisation of the thrombotic-occluded veins and indicate the reduction of valvular incompetence rate, secondary to venous thrombosis .…”
Section: Introductionmentioning
confidence: 99%
“…[20] hanno condotto uno studio con controllo venografico per confrontare l'efficacia e la tollerabilità dei due approcci terapeutici alternativi su 165 pazienti con TVP. Il primo gruppo ha ricevuto un trattamento con ENF e anticoagulanti orali, con dosaggio aggiustato in base agli esami di laboratorio, mentre il secondo gruppo ha ricevuto enoxaparina, somministrata per due volte al dì nella prima settimana, in regime di ricovero ospedaliero, e in unica somministrazione giornaliera per 90 giorni dopo la dimissione.…”
Section: Efficacia Clinicaunclassified